2016
DOI: 10.3996/012015-jfwm-004
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Habitat Models for Northern Long-Eared Bats from Historical Detection Data: A Case Study Using the Fernow Experimental Forest

Abstract: The listing of the northern long-eared bat (Myotis septentrionalis) as federally threatened under the Endangered Species Act following severe population declines from white-nose syndrome presents considerable challenges to natural resource managers. Because the northern long-eared bat is a forest habitat generalist, development of effective conservation measures will depend on appropriate understanding of its habitat relationships at individual locations. However, severely reduced population sizes make gatheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…For our study, elevation likely served as a surrogate measure of topographic position. Given the undulating terrain in MCNP, we suggest that habitat associations observed for non‐reproductive females in spring (i.e., more mature forests with higher canopy cover situated in more sheltered ravine bottoms) were reflective of forest conditions promoting cooler microclimates insides roost trees (Ford et al ). Roost trees with reduced solar exposure surrounded by decreased ambient temperatures should be expected to facilitate use of daytime torpor in tree roosting bats (Turbill et al , Willis et al , Ruczyński ), especially for non‐reproductive females during the staging period when food supplies are likely scarce and weather conditions frequently inclement.…”
Section: Discussionmentioning
confidence: 99%
“…For our study, elevation likely served as a surrogate measure of topographic position. Given the undulating terrain in MCNP, we suggest that habitat associations observed for non‐reproductive females in spring (i.e., more mature forests with higher canopy cover situated in more sheltered ravine bottoms) were reflective of forest conditions promoting cooler microclimates insides roost trees (Ford et al ). Roost trees with reduced solar exposure surrounded by decreased ambient temperatures should be expected to facilitate use of daytime torpor in tree roosting bats (Turbill et al , Willis et al , Ruczyński ), especially for non‐reproductive females during the staging period when food supplies are likely scarce and weather conditions frequently inclement.…”
Section: Discussionmentioning
confidence: 99%
“…In all burn conditions, activity had a slightly positive relationship with increased elevation. Because burn intensity is greater on upper slopes (Mladenoff 1999), reductions in clutter that improve foraging condition may have negated previously negative relationships with bat activity and increasing elevation in the central Appalachians at elevations where oak-dominated types are replaced by northern hardwood to the west on the Allegheny Plareau (Ford et al 2005;Ford et al 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Of the suite of bats in the region, the endangered Indiana bat (Myotis sodalis [Miller and Allen, 1928]; MYSO) and the threatened northern long-eared bat (Myotis septentrionalis [Trouessart, 1897]; MYSE) are two species potentially impacted by prescribed fire (Austin et al 2018b). Prescribed fire use may alter non-hibernating season day-roosts, (i.e., trees and snags) or change foraging habitat conditions (Carter and Ford 2002;Perry 2012;Ford et al 2016b;Silvis and Perry 2016b). Because there has been limited work examining the relationships of these and other bat species in the central Appalachians relative to the return of fire as a prescriptive tool, land managers are often challenged to show that burning is not additive in negative impacts to these already stressed species (Johnson et al 2010b;Ford et al 2016a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of multi-scale analyses in examining roost selection of North American bats has been achieved for foliageroosting species (Veilleux et al 2004;Limpert et al 2007;Hein et al 2008) and select Myotis species (Arnett and Hayes 2009;Lacki et al 2010;Hammond et al 2016;Jachowski et al 2016), with a range of landscape patterns found to be beneficial depending on species and geographic location. Comparative studies are limited on landscape-level selection of tree roosts by the northern long-eared bat, Myotis septentrionalis (Pauli et al 2015;Ford et al 2016); a threatened species experiencing severe population declines across much of its distribution in North America (USDI 2015).…”
Section: Introductionmentioning
confidence: 99%